KARAKTERISTIK PROFESI DAN PROFESI HUKUM KAITANNYA DENGAN ERA DIGITALISASI - Raudlatul Jannah Mbejo Golu; Mulya Wibisono; Anam Muhyidin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research will explain the characteristics of the legal profession that will be associated with the digitalization era, where technological developments will directly impact law offices, courts, police, prosecutors and other law enforcement agencies which will increasingly need more legal information engineers. This can be seen from the existence of IT experts who also understand the law, who understand the law are expected to be able to anticipate possible negative impacts from the use of electronics and the internet/cyberspace. This kind of expertise is also important for law enforcement institutions where they must be able to provide legal services that can help the community, government and legislative institutions as regulators to see from a different perspective the development of the world of law enforcement. Therefore, joint efforts are needed from all parties to take advantage of opportunities and overcome these challenges. With strong collaboration and commitment, digital transformation can bring positive changes to the world of law and improve the quality of legal services for society.